Pengaruh pengetahuan pajak, kesadaran pajak dan tarif pajak terhadap kepatuhan pajak wajib Pajak UKM Kota Jambi - Fitrini Mansur; Reka Maiyarni; Eko Prasetyo; Riski Hernando (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2022)
This study aims to determine the compliance of taxpayers with their obligations to pay taxes. The theoretical concepts tested are tax knowledge, tax awareness, and tax compliance rates. Data was collected through questionnaires on 100 small and medium-sized businesses in the printing and screen printing sector. Multiple regression analysis was used to test the hypothesis. The results showed that tax knowledge, tax awareness, and tax rates positively affected taxpayer compliance. This research can assist the government in determining the policies needed to improve tax compliance. These results indicate that the government needs to increase tax awareness and attention to tax rates to improve tax compliance in fulfilling its tax obligations.